Sistem Pelayanan Pengaduan Masyarakat Berbasis Web Di Kecamatan Medan Tuntungan - Sembiring, Ikhsan Diridoina; Sondang, Sondang; Sujarwo, Sujarwo; Astuti, Yuniar Andi (Jurnal Armada Informatika, 2025)
Public complaint services are a crucial aspect in realizing transparent, responsive, and accountable governance. To date, the complaint process in Kecamatan Medan Tuntungan has been carried out conventionally through face-to-face interactions and unstructured social media channels, resulting in challenges in recording, handling, and following up on public complaints. This study aims to design and develop a web-based public complaint service system that facilitates residents in submitting reports, complaints, and aspirations in an easy, fast, and well-documented manner. The system was developed using the waterfall method, which consists of the stages of requirements analysis, system design, implementation, and testing. The results of the study indicate that the system is capable of providing convenience for the community in submitting complaints, while also assisting the district office in managing reports in a more structured, transparent, and effective way. With the implementation of this system, it is expected that the quality of public services in Kecamatan Medan Tuntungan will improve, while also strengthening community participation in regional development.